2 - A Case for ‘Prevailing Ecology’ as Premium Determinant in Home-Based Child Care Conceptualisation and Measurements - Peter Atakuma Agbodza (African Sociological Review, 2016)
This paper is based on a 22-month ethnographic study of child care practices of Tongu Ewe mothers located in Dzemeni a migrant, lakeside community in Ghana. It asserts the relevance of establishing the ecology for childcare as a premium yardstick within the practice of conceptualisation and measurement of childcare practices of mothers. It builds a case from the analysis of definitions and concepts in care literature. Notable among these are the works of Fisher and Tronto, Folbre, Longhurst, Oppong, Van Esterik among others. These are juxtaposed against the definitions and conceptual frameworks used to analyse child care in the Dzemeni study. The ethics of care framework propounded by Fisher and Tronto (1990) and the conceptual framework on care developed in 1995 by the UNICEF/Cornell University are examined in terms of their suitability as ‘models’ for assessing childcare practices universally. The paper proposes a re-evaluation of the tools of assessment of home-based child care costs in order to be able to construct a more encompassing framework.